Insects and Colors between Art and Natural History - Mandrij, V.E.,; Simonini, Giulia, (Early Modern History and Modern History E-Books Online, Collection 2024., 2025)
This book explores how European naturalists and artists perceived, investigated, and presented the relationship between insects and colors from the late sixteenth to the late eighteenth century. The contributors to this volume examine the creative methods and strategies that were developed to record color-related information about insects through studies on Hoefnagel's glazed metal and hand-coloring practices; the lepidochromy technique used in paintings by Marseus van Schriek and later naturalists; the representation of sexual dimorphism of color and variable color of caterpillars in the images of Goedaert, Merian, Albin, and Rösel von Rosenhof; the painting-by-numbers technique applied to Schäffer's bookplates on Regensburg insects; Schiffermüller's watercolor originals of caterpillars; and finally, the color fading of exotic cabinet specimens and how this issue was tackled by Abbot and Smith. The volume is lavishly illustrated with rare and unpublished images and offers new insights into the interrelation between natural history and visual practices concerning the color of insects, with a special focus on butterflies and moths. Contributors are Harald Bruckner, Kay Etheridge, Beth Fowkes Tobin, Stefanie Jovanovic-Kruspel, Karin Leonhard, V.E. Mandrij, Kimberly Schenck, Stacey Sell, Giulia Simonini, and Friedrich Steinle. See Less